Um instrumento para análise de atividades de livros didáticos de Ciências da Natureza - Ana Elisa Braga (2024)
The textbook is one of the main pedagogical resources that assists both the teacher and the student in the teaching and learning process. We believe that many of the guiding principles of normative documents for pedagogical renewal are reaching schools through textbooks. At BNCC, scientific literacy appears as one of the structuring axes for the area of Education in Natural Sciences and scientific research as one of the paths that contributes to the development of scientific literacy. In this sense, this research has as its central objective to analyze contributions that an instrument for analyzing textbook activities can offer the teacher to assist him in the selection of activities to compose a teaching plan committed to the students' scientific literacy process. To this end, we adapted an instrument proposed by the APEC Group in 2011 to analyze science teaching and learning activities. The original instrument allows the identification of different types of activities and their objectives to help the teacher in carrying out work in the classroom. In the adaptation we carried out, we added objectives that help the teacher in identifying investigative characteristics of activities that can contribute to the students' literacy/scientific literacy process. To reflect on the potential of this instrument, we will analyze the activities proposed in a collection of science textbooks approved in the last PNLD. Therefore, we bet that by analyzing the activities present in these books we will be able to not only identify the content of the activities, but also identify their potential for promoting students' scientific literacy.